QUALITY CONTROL EVALUATION OF IN HOUSE PREPARED POLYHERBAL AYURVEDIC FORMULATION SAPTAVIMSATIKA GUGGLU - Nainwal, Pankaj (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Introduction: Plants and their constituent are having potential of treating any human suffering in form of disease. Various combination of plant extract is used as a remedy for treating these disorders. However the usage and dose of these extract which are in random and unspecified is a big challenge for acceptance as a medicine till not get standardized. The most important Ayurvedic drugs i.e. Saptavimsatika guggulu had been selected from Ayurvedic famous books named API Ayurvedic Monographs for Phytochemical and Physicochemical study. This Ayurvedic drugs is mainly and commonly used in the treatment of heart, skin and stomach related disease. Drug preparation was done during an event organized by our University under theme Rx-Thon. Methods: Physico and Phytochemical study both had been done in the labs of School of Pharmacy, Graphic Era Hill University. Values like Exractive value, Ash value, Mosture content, pH values, True density, bulk density, angle of repose, carr's index, hausner's ratio, Florescence analysis, TLC was covered in the study Result: Phytochemical study revealed that reducing sugars, tannin, phenolic compounds, saponin glycosides, and gum were present in the sample. Various physico-chemical parameter had been studied in the standardization procedures. The extractive, ash values, florescence analysis was done and was compared to reference standard. Conclusion: The physicochemical standardization of polyherbal formulation Saptavimsatika guggulu was carried out. The individual ingredients of the formulation were authenticated and standardized as per WHO guidelines and Indian Herbal Pharmacopoeia. The in-house formulation was prepared and studied for various physicochemical properties. Although no marketed sample is available hence a porbability is made under standard evaluation parameter to launch this product in market for sale.